2011
DOI: 10.1097/fbp.0b013e32834d6279
|View full text |Cite
|
Sign up to set email alerts
|

Impulsive behaviour in rats induced by intracortical DOI infusions is antagonized by co-administration of an mGlu2/3 receptor agonist

Abstract: The orbitofrontal cortex (OFC) and the medial prefrontal cortex (mPFC) modulate impulsive behaviours. Serotonin [5-hydroxytryptamine (5-HT)] 2A receptors have also been implicated in impulsivity and govern antagonistic interactions with metabotropic glutamate (mGlu)2/3 receptors. This study examined the interactions between 5-HT2A and mGlu2/3 receptors in the OFC and mPFC with relevance to impulsive choice and impulsive action. Impulsive choice was assessed in Lister Hooded rats, trained in a delay-discounting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 0 publications
2
28
0
Order By: Relevance
“…We discovered that HI rats exhibited higher sensitivity to the effects of the preferential 5-HT 2A R agonist DOI (5-HT 2A R-mediated head-twitches) and to the effects of the selective 5-HT 2A R antagonist M100907 (suppression of premature responses). Our finding that HI action tracks with high cortical 5-HT 2A R density, particularly within the mPFC, is consistent with microinfusion studies that validate the importance of the 5-HT 2A R in the mPFC for both generating the head-twitch response (Willins and Meltzer, 1997) and mediating impulsive action Winstanley et al, 2003;Wischhof et al, 2011; but see Robinson et al, 2008). Furthermore, the higher level of 5-HT 2A R/PSD95 association in the mPFC of HI rats relative to LI rats suggests that factors that control the functional status of the 5-HT 2A R in mPFC may drive in part the predisposition to inherent impulsive action.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…We discovered that HI rats exhibited higher sensitivity to the effects of the preferential 5-HT 2A R agonist DOI (5-HT 2A R-mediated head-twitches) and to the effects of the selective 5-HT 2A R antagonist M100907 (suppression of premature responses). Our finding that HI action tracks with high cortical 5-HT 2A R density, particularly within the mPFC, is consistent with microinfusion studies that validate the importance of the 5-HT 2A R in the mPFC for both generating the head-twitch response (Willins and Meltzer, 1997) and mediating impulsive action Winstanley et al, 2003;Wischhof et al, 2011; but see Robinson et al, 2008). Furthermore, the higher level of 5-HT 2A R/PSD95 association in the mPFC of HI rats relative to LI rats suggests that factors that control the functional status of the 5-HT 2A R in mPFC may drive in part the predisposition to inherent impulsive action.…”
Section: Discussionsupporting
confidence: 85%
“…The quantity of tissue required to conduct receptor binding assays necessitated the use of the whole frontal cortex that comprises not only the mPFC, but also cortical subregions that putatively could have limited or opposing functional involvement in inhibitory control. Thus, 5-HT 2A R density determined in whole frontal cortex may underestimate differences between impulsive action phenotypes within functionally relevant frontal cortical subregions such as the mPFC that mediates DOI-induced head-twitches (Willins and Meltzer, 1997) and motor impulsivity Winstanley et al, 2003;Wischhof et al, 2011). Interestingly, we found that HI rats expressed higher 5-HT 2A R protein expression assessed by immunodetection methods in the whole frontal cortex as well as the mPFC.…”
Section: -Ht 2a Receptor In Impulsive Actionmentioning
confidence: 70%
See 2 more Smart Citations
“…Their findings suggest that in frontal cortex mGlu2/3 receptors negatively regulate the G q phospholipase C3 pathway that is activated by 5-HT 2A receptors. Wischhof et al (2011) examined interactions between 5-HT 2A and mGlu2/3 receptors in the orbitofrontal cortex (OFC) and mPFC with respect to impulsive choice and impulsive action in Lister Hooded rats. Impulsive choice was assessed in rats trained in a delay-discounting T-maze task, after bilateral infra-OFC infusions of DOI or the mGlu2/3 agonist LY379268.…”
Section: Role Of Glutamatementioning
confidence: 99%